Matemática recreativa en el estudio de la trigonometría - Vivanco Espinoza, Flor Cristina (2024)
Recreational mathematics is a didactic strategy that allows teaching in a playful and enjoyable manner. Therefore, this research aims to determine the importance and benefits of recreational mathematics in the study of trigonometry in Second Unified General Baccalaureate. Documentary research has been used, compiling and systematizing information from documentary sources using the filing technique and mixed cards. Through this, it was possible to show that recreational mathematics favors problem-solving with various benefits, and that the use of recreational activities provides contributions that enhance the teaching-learning process of trigonometry compared to traditional methods. This strategy helps create an optimal environment for the educational process, in which significant skills and abilities can be strengthened and developed in students while effectively and optimally learning trigonometry content. Key Words: Recreational mathematics, playful, learning, activities, trigonometry.